2005
DOI: 10.1038/sj.npp.1300849
|View full text |Cite
|
Sign up to set email alerts
|

Motor Stimulant Effects of Ethanol Injected into the Substantia Nigra Pars Reticulata: Importance of Catalase-Mediated Metabolism and the Role of Acetaldehyde

Abstract: A series of experiments was conducted to investigate the locomotor effects of local injections of ethanol and the ethanol metabolite, acetaldehyde, into substantia nigra pars reticulata (SNr). Infusions of ethanol into SNr resulted in a dose-related increase in locomotor activity, with maximal effects at a dose of 1.4 mmol. Ethanol injected into a control site dorsal to substantia nigra failed to stimulate locomotion, and another inactive site was identified in brainstem areas posterior to substantia nigra. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 105 publications
6
47
0
1
Order By: Relevance
“…The dose-response curve for Sal has an inverted U-shaped profile, with a peak at the 30.0-pmol dose. The profile of this plot is similar to those obtained in the posterior VTA for Sal (Rodd et al 2008), ethanol (Rodd et al 2004a, b), and ACH (Rodd et al 2004b;Rodd-Henricks et al 2002) in ICSA experiments and for ethanol in the substantia nigra pars reticulata (Arizzi-LaFrance et al 2006) in locomotor activity studies in rats. It is important to realize that the maximum effect on motor activity was obtained in our present study with the 30.0-pmol dose, which is clearly lower than that previously reported by our group for ethanol (150 nmol) and ACH (250 nmol; Sánchez-Catalán et al 2009).…”
Section: Discussionsupporting
confidence: 62%
“…The dose-response curve for Sal has an inverted U-shaped profile, with a peak at the 30.0-pmol dose. The profile of this plot is similar to those obtained in the posterior VTA for Sal (Rodd et al 2008), ethanol (Rodd et al 2004a, b), and ACH (Rodd et al 2004b;Rodd-Henricks et al 2002) in ICSA experiments and for ethanol in the substantia nigra pars reticulata (Arizzi-LaFrance et al 2006) in locomotor activity studies in rats. It is important to realize that the maximum effect on motor activity was obtained in our present study with the 30.0-pmol dose, which is clearly lower than that previously reported by our group for ethanol (150 nmol) and ACH (250 nmol; Sánchez-Catalán et al 2009).…”
Section: Discussionsupporting
confidence: 62%
“…Previously, Arizzi-LaFrance et al (2006) had reported that microinjections of ethanol or ACH into the SNr increased the locomotor activity of rats at doses higher than 350 nmol. The effective dose in our study was slightly lower than those reported in the aforementioned study: in our experiments, a 75-nmol dose of ethanol and a 250-nmol dose of ACH effectively and significantly increased the locomotor activity of rats.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was designed to assess the effects of intra-VTA injections of vehicle, ethanol (75 and 150 nmol), and ACH (25 and 250 nmol) on locomotor activity. Doses of ethanol and ACH were selected according to the dose-effect curves reported by Arizzi-LaFrance et al (2006) in their study on the locomotor-activating effects of the intranigral administration of these compounds. Based on the results of this experiment, the 150-nmol dose of ethanol and the 250-nmol dose of ACH were used in experiments 2 and 3b, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted earlier, the first product coming from brain-EtOH metabolism by the activity of Compound I is acetaldehyde. Acetaldehyde is a psychoactive molecule that, when administered centrally, exerts a broad range of behavioral (Arizzi-LaFrance et al, 2006;Rodd-Henricks et al, 2002;Smith et al, 1984) and neurochemical (Diana et al, 2008;Enrico et al, 2009;Foddai et al, 2004;Sirca et al, 2011) effects that are similar to those induced by EtOH in rodents. For this reason, it has been proposed that brain-EtOH-derived acetaldehyde could play a role in some of the psychopharmacological effects caused by EtOH.…”
Section: Discussionmentioning
confidence: 99%